First results of the DIVING3D survey of bright galaxies in the local universe: The mini-DIVING3D sample. Issue Volume 15:Issue S359(2020) (March 2019) - Menezes, R. B.; Steiner, J. E.; Ricci, T. V.; da Silva, Patrícia; Nicolazzi, D. M.
Abstract: We present the first results of the Deep Integral Field Spectroscopy View of Nuclei of Galaxies (DIVING 3 D ) survey, obtained from the analysis of the nuclear emission-line spectra of a sub-sample we call mini-DIVING 3 D, including all southern galaxies with B < 11.2 and |b| >15°. In comparison with previous studies, very few galaxies were classified as Transition objects. A possible explanation is that at least part of the Transition objects are composite systems, with a central low-ionization nuclear emission-line region (LINER) contaminated by the emission from circumnuclear H II regions. The high spatial resolution of the DIVING 3 D survey allowed us to isolate the nuclear emission from circumnuclear contaminations, reducing the number of Transition objects.